Development of Standardized Clinical Assessment and Management Plans (SCAMPs) in Plastic and Reconstructive Surgery - Caterson, Stephanie A. (Plast Reconstr Surg Glob Open, 2015)
BACKGROUND: With rising cost of healthcare, there is an urgent need for developing effective and economical streamlined care. In clinical situations with limited data or conflicting evidence-based data, there is significant institutional and individual practice variation. Quality improvement with the use of Standardized Clinical Assessment and Management Plans (SCAMPs) might be beneficial in such scenarios. The SCAMPs method has never before been reported to be utilized in plastic surgery. METHODS: The topic of immediate breast reconstruction was identified as a possible SCAMPs project. The initial stages of SCAMPs development, including planning and implementation, were entered. The SCAMP Champion, along with the SCAMPs support team, developed targeted data statements. The SCAMP was then written and a decision-tree algorithm was built. Buy-in was obtained from the Division of Plastic Surgery and a SCAMPs data form was generated to collect data. RESULTS: Decisions pertaining to “immediate implant-based breast reconstruction” were approved as an acceptable topic for SCAMPs development. Nine targeted data statements were made based on the clinical decision points within the SCAMP. The SCAMP algorithm, and the SDF, required multiple revisions. Ultimately, the SCAMP was effectively implemented with multiple iterations in data collection. CONCLUSIONS: Full execution of the SCAMP may allow better-defined selection criteria for this complex patient population. Deviations from the SCAMP may allow for improvement of the SCAMP and facilitate consensus within the Division. Iterative and adaptive quality improvement utilizing SCAMPs creates an opportunity to reduce cost by improving knowledge about best practice.